Promoting EFL Pre-Service Teachers' Language Management Skills Using an Action Learning Program - Aya Khedr; جيهان محمود رزق البسونى; ولاء محمد الحناوي (Faculty of Education - Port Said University, 2023)
The current study examined the impact of action learning program to promote some EFL language management skills among EFL pre-service teachers at Port Said Faculty of Education. The problem of the study was identified in the preservice teachers' weak performance of verbal and nonverbal language management skills (e.g., instructional communication and instruction giving skills) during instruction in the teaching practicum. The study adopted the mixed method research with a design of concurrent triangulation. The subjects of the study were (36) EFL preservice teachers in the fourth year, general education. They were divided into two groups: experimental group (N=16), and control group (N=20). An observation rating scale, a scenario-based test, and a semi-structured interview instruments were developed and conducted for collecting data. The results of the study showed that there were statistically significant differences at 0.01 level between the mean ranks of the control and experimental groups' scores on the post-assessment in favor of the experimental group in overall language management skills as well as in each main skill separately. The findings of the present study revealed that a program based on action learning has a positive impact on promoting language management skills among EFL preservice teachers. Therefore, the proposed program can be adopted by EFL preservice, and in-service teachers for developing their language management skills in the classroom.